2017
DOI: 10.1111/jocn.13754
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of occupational burnout among nurses: a dominance analysis of job stressors

Abstract: Understanding the relative effect of job stressors may help identify fruitful areas for intervention and improve nurse recruitment and retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 38 publications
4
27
0
1
Order By: Relevance
“…Indeed, when job satisfaction increases, productivity and performance increase as well (Sahin, Akyurek, & Yavuz, 2014). From this perspective, development of nurses' professional competencies is an important factor affecting their service quality (Sahin et al, 2014;Sun et al, 2017;Wilkes, Cowin, & Johnson, 2015). Along with inadequacy in the number of nurses, difficult working conditions, irregular and long working hours, and work pressure cause significant problems in the nursing profession (Lee, Dai, & McCreary, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, when job satisfaction increases, productivity and performance increase as well (Sahin, Akyurek, & Yavuz, 2014). From this perspective, development of nurses' professional competencies is an important factor affecting their service quality (Sahin et al, 2014;Sun et al, 2017;Wilkes, Cowin, & Johnson, 2015). Along with inadequacy in the number of nurses, difficult working conditions, irregular and long working hours, and work pressure cause significant problems in the nursing profession (Lee, Dai, & McCreary, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, dynamic changes in the work environment and psychosocial job characteristics significantly impacted and predicted employee burnout (Pisanti et al, ). Yet another study found interpersonal relationships and management problems as the strongest predictors of burnout (Sun et al, ). Therefore, for the purposes and conceptual clarity of this research, we decided to classify predictors of burnout arising from internal (work‐related, such as internal conflict and job insecurity) and external pressures (patient induced outcomes).…”
Section: Introductionmentioning
confidence: 99%
“…As Hayes B's a review, the relationship of nurses with physicians had the highest negative influence on job burnout [13]. Sun JW confirmed that interpersonal relationships and management issues most strongly predicted participants' burnout [14]. Furthermore, many studies verified the key value of connections with colleagues to job burnout, such as those related to interpersonal justice [15], interpersonal conflicts [16], and group noncooperation [17].…”
Section: Introductionmentioning
confidence: 93%